Cerebellar Vermis and Midbrain Hypoplasia Upon Conditional Deletion of Chd7 from the Embryonic Mid-Hindbrain Region - Donovan, Alex P. A.; Yu, Tian; Ellegood, Jacob; Riegman, Kimberley L. H.; de Geus, Christa; van Ravenswaaij-Arts, Conny; Fernandes, Cathy; Lerch, Jason P.; Basson, M. Albert (Frontiers in Neuroanatomy, 2017)
Reduced Fibroblast Growth Factor (FGF) signaling from the mid-hindbrain or isthmus organizer (IsO) during early embryonic development results in hypoplasia of the midbrain and cerebellar vermis. We previously reported evidence for reduced Fgf8 expression and FGF signaling in the mid-hindbrain region of embryos heterozygous for Chd7, the gene mutated in CHARGE (Coloboma, Heart defects, choanal Atresia, Retarded growth and development, Genitourinary anomalies and Ear defects) syndrome. However, Chd7+/- animals only exhibit mild cerebellar vermis anomalies. As homozygous deletion of Chd7 is embryonic lethal, we conditionally deleted Chd7 from the early embryonic mid-hindbrain region to identify the function of CHD7 in mid-hindbrain development. Using a combination of high resolution structural MRI and histology, we report striking midbrain and cerebellar vermis hypoplasia in the homozygous conditional mutants. We show that cerebellar vermis hypoplasia is associated with reduced embryonic Fgf8 expression and an expanded roof plate in rhombomere 1. These findings identify an essential role for Chd7 in regulating mid-hindbrain development via Fgf8.